‘Historiese improvisasie’: Verhalende geschiedschrijving in de roman Skepelinge. Aanloop tot ‘n roman (2017) van Karel Schoeman - Bandov, Toni (Acta Neerlandica, 2023)
Karel Schoeman’s fictional historiography Skepelinge. Aanloop tot ‘n roman (2017) offersan alternative representation of the early colonial history at Cape of Good Hope with itspronounced emphasis on marginalized individuals or groups and unrealized socialpotentials of the (hybridized) colonial society. By activating forgotten or concealednarratives and alternative visions of history and by writing from the position of historical‘losers’, the text also contains an anti-colonial potential and reveals a constant ideologicalstruggle in the historiographical representations. The novel therefore fits into the postapartheid literary trend of rewriting (national) history, parodizing canonical texts andcriticizing the ideological strongholds of Afrikaner nationalism.